National Survey of US Long-Haul Truck Driver Health and Injury: health behaviors - Birdsey, Jan; Sieber, W Karl; Chen, Guang X; Hitchcock, Edward M; Lincoln, Jennifer E; Nakata, Akinori; Robinson, Cynthia F; Sweeney, Marie H (Journal of occupational and environmental medicine, 2015)
To compare selected health behaviors and body mass index (modifiable risk factors) of US long-haul truck drivers to the US working population by sex. The National Survey of US Long-Haul Truck Driver Health and Injury interviewed a nationally representative sample of long-haul truck drivers (n = 1265) at truck stops. Age-adjusted results were compared with national health surveys. Compared with US workers, drivers had significantly higher body mass index, current cigarette use, and pack-years of smoking; lower prevalence of annual influenza vaccination; and generally lower alcohol consumption. Physical activity level was low for most drivers, and 25% had never had their cholesterol levels tested. Working conditions common to long-haul trucking may create significant barriers to certain healthy behaviors; thus, transportation and health professionals should address the unique work environment when developing interventions for long-haul drivers.